The strategy of PT. Kereta Api Logistik Maintaining Brand Image - Nanda Anggun Pratiwi; Susi Yunarti (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
This research examines the branding strategy of PT Kereta Api Logistik (KALOG), a state-owned logistics company in Indonesia, focusing on how operational innovations and the